Low IgG Seroconversion among Persons Vaccinated against Measles, Republic of Congo - Yanne Vanessa Thiécesse Mavoungou; Léa Gwladys Gangoué; Félix Koukouikila-Koussounda; Cynthia Badzi Nkoua; Pembe Issamou Mayengue; Jean-Medard Kankou; Pathou Christelle Kiminou; Princesse Mahoukou; Louis Régis Dossou-Yovo; Gabriel Ahombo; Fabien Roch Niama (Emerging Infectious Diseases)
We report a low (38.7%; p<0.0001) level of IgG seroconversion in patients who were positive for measles virus IgM in the Republic of Congo, despite a history of vaccination. Considering this country’s recurring measles epidemics, more effective immunization strategies, including vaccine delivery methods, are needed to prevent measles outbreaks.